The effects of international logistics in global value chain trade - Zaninović, Petra Adelajda; Bugarčić, Filip Ž. (Journal of Business Economics and Management, 2023)
The current empirical literature shows that logistics plays a vital role in increasing the total volume of international trade. However, there is scarce literature on the impact of logistics performance on global value chain trade. Therefore, the objective of this paper is to investigate the effect of logistics performance on global value chain trade, measured by the value-added exports. The empirical specification of this paper is based on the structural gravity model of international trade. The analysis is based on biennial panel data on bilateral trade flows for the EU-15, CEE, and the Western Balkans and covers the period from 2010 to 2018. The model is estimated with a Poisson Pseudo Maximum Likelihood Estimator. The results show that logistics performance appears to have significant positive effects on global value chain trade and that the logistics performance of the partner country plays a more critical role than the logistics performance of the reporting country. Institutional quality matters greatly for global value chain trade. Individual differences in the observed variables were found between selected groups of countries. The need to improve logistics performance and invest in knowledge and technology will help countries improve in value chains, along with adequate institutional support.